2022
DOI: 10.3390/antiox11102048
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine Supplementation Alleviates Lipopolysaccharide-Triggered Adaptive Inflammatory Response and Modulates Energy State via Suppression of NFκB/p38 MAPK/AMPK Signaling in Rumen Epithelial Cells of Goats

Abstract: Studies have shown that exogenous thiamine (THI) supplementation can alleviate inflammation and promote rumen epithelial development in goats and cows. This research aimed to evaluate the effect of THI supplementation on LPS-induced inflammation and energy metabolic dysregulation in RECs of goats. Cells were stimulated with either 5 μg/mL THI for 18 h (THI group) or with 5 μg/mL LPS for 6 h (LPS group). The CON group was stimulated with DMEM/F-12 medium without THI for 18 h. The LPTH group was pretreated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…As the activity of MAPKs increases, especially p38 MAPK, inflammatory mediators are also enhanced at the transcriptional and translational levels to enhance the inflammatory response [ 54 ]. It is well documented that stimulation of RECs for 6 h using LPS (10 µg/mL) can activate the MAPK pathway [ 43 ], consistent with our results, while GRECs (goat rumen epithelial cells) required LPS (5 µg/mL) stimulation for 6 h at a lower dose to activate [ 55 ]. The results of the experiment indicate the activation of the NF-κB and MAPK signaling pathways through p65 translocation into the nucleus following LPS stimulation.…”
Section: Discussionsupporting
confidence: 91%
“…As the activity of MAPKs increases, especially p38 MAPK, inflammatory mediators are also enhanced at the transcriptional and translational levels to enhance the inflammatory response [ 54 ]. It is well documented that stimulation of RECs for 6 h using LPS (10 µg/mL) can activate the MAPK pathway [ 43 ], consistent with our results, while GRECs (goat rumen epithelial cells) required LPS (5 µg/mL) stimulation for 6 h at a lower dose to activate [ 55 ]. The results of the experiment indicate the activation of the NF-κB and MAPK signaling pathways through p65 translocation into the nucleus following LPS stimulation.…”
Section: Discussionsupporting
confidence: 91%
“…25 More, the modulation of thiamine metabolism inhibits the development of inflammation in a variety of diseases. 26,27 These findings provide convincing evidence for the effectiveness of WZYD in the treatment of CNAG in the clinical setting by suppressing inflammation and modulating core metabolism process. To confirm the effect of WZYD on inflammatory factors in patients with CNAG, patient serum was examined, and ELISA results demonstrated that WZYD treatment effectively reduced serum levels of TNF-α, IL-10, and COX-2.…”
Section: Discussionmentioning
confidence: 66%
“…A high concentrate diet can upregulate the expression of IL-1β, IL-2, IL-22, and other in ammatory factors [52]. In vitro studies have shown that LPS can signi cantly increase the level of IL-6 and the phosphorylation of NF-κB/P38 and MAPKs in rumen epithelial cells [53]. These results suggest that the LPS-induced overactivation of NF-κB and MAPKs mediates rumen in ammation during subacute acidosis.…”
Section: Discussionmentioning
confidence: 88%